Four new species of Chaetogastra (Melastomeae, Melastomataceae) from Southern Brazil - Meyer, Fabrício Schmitz; Goldenberg, Renato (Phytotaxa, 2016)
Four new species of Chaetogastra are described: C. cordeiroi, C. crassifolia, C. cristaensis and C. riograndensis, recognized during a taxonomic study of the genus in Brazil. All of them come from southern Brazil, in the Atlantic Forest biome, at the states of Rio Grande do Sul, Santa Catarina and Paraná. All four species are threatened, under different categories.